Nursing Advanced Skills - Open RN, Open Resources for Nursing (Open textbook library., 2023)
This textbook is an open educational resource with CC-BY licensing developed specifically for prelicensure nursing students. The e-book and downloadable versions are free. Affordable print versions are published in collaboration with XanEdu and available on Amazon and in college bookstores. Content is based on the Wisconsin Technical College System (WTCS) statewide nursing curriculum for the Nursing Advanced Skills course (543-112) and the NCLEX-RN Test Plan. 1 Content includes advanced skills for registered nurses, such as intravenous infusion, blood product administration, management of central lines and chest tube systems, basic electrocardiogram interpretation, and nasogastric/feeding tube insertion, and builds on basic nursing skills discussed in the Open RN Nursing Skills OER textbook.